2021
DOI: 10.1186/s12960-021-00566-3
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional collaboration among health professionals in cleft lip and palate treatment and care in the public health sector of South Africa

Abstract: Background Collaboration among different categories of health professionals is essential for quality patient care, especially for individuals with cleft lip and palate (CLP). This study examined interprofessional collaboration (IPC) among health professionals in all CLP specialised centres in South Africa’s public health sector. Methods During 2017, a survey was conducted among health professionals at all the specialised CLP centres in South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Only 6 of the 11 centres provided written, standard treatment protocols for CLP (Study Component 2) [ 15 ]. The audit of treatment and care provision revealed gaps, and the types of treatment provided was influenced by the categories of health care professionals in each centre [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 6 of the 11 centres provided written, standard treatment protocols for CLP (Study Component 2) [ 15 ]. The audit of treatment and care provision revealed gaps, and the types of treatment provided was influenced by the categories of health care professionals in each centre [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…This implies that patients and their caregivers are part of the team. However, the study found that IPC was sub-optimal [ 19 ]. The teams of health care professionals who managed individuals with CLP appeared to work in silos, and doctors tended to dominate the health care teams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that female physicians have outnumbered male participants in leading IPC programs [ 14 ]. Additionally, a study by P. Hlongwa indicates that females may have enhanced competence in some areas [ 15 ]. Furthermore, a study by Akan et al found that the risk perception of males was significantly lower than that of females, indicating that females may have a better understanding of the risks associated with infection, which could contribute to their enhanced competence in IPC [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of cleft lip and palate requires a comprehensive multidisciplinary approach that mainly focuses on maxillofacial, orthodontics, dentistry, oral prosthetics, otolaryngology, speech pathology, pediatrics, nursing, genetics, and psychology (Hlongwa and Rispel, 2021). Patients with cleft lip and palate require multiple surgical treatments, complex medications, and long-term speech therapy (Jerome et al, 2017).…”
Section: Discussionmentioning
confidence: 99%